'The business end': Neoliberal policy reforms and biomedical residualism in frontline community mental health practice in England. (April 2020) - Moth, Rich
Mental health policy initiatives in England over the last three decades have led to significant restructuring of statutory service provision. One feature of this has been the reconfiguration of NHS mental health services to align with the requirements of internal and external markets. Based on findings from 12 months' ethnographic fieldwork within one mainstay of NHS statutory provision, the community mental health team, this paper examines the effects of these neoliberal policy and service reforms on professional practice and conceptualizations of mental distress. The paper begins with an account of the restructuring of the labour process in community mental health services. This utilizes the notion of 'strenuous welfarism' to describe an organizational context characterized by escalating performance management, deskilling of professional practice and the intensification of mental health work. Increasingly prominent aspects of managerialism and marketization disrupted attempts by mental health practitioners to sustain supportive and mutual structures with colleagues and engage service users in therapeutic and relationship-based forms of practice. Moreover, organizational processes increasingly recast service users as individual consumers 'responsibilized' to manage their own risk or subject to increasingly coercive measures when perceived to have failed to do so. Consequently, biomedical orientations were remobilized in practice in spite of a purported shift in policy discourse towards more socially inclusive approaches. The term 'biomedical residualism' is coined to describe this phenomenon. However, instances of ethical professionalism that reflected resistance to these residualized modes of practice were also visible.